Penerapan House of Quality (HoQ) Untuk Peningkatan Kualitas Produk Pada UMKM Salad Buah di Kota Batam - Sumitro; Lawi, Ansarullah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Universal, 2024)
Fruit Salad SMEs in Batam City face significant challenges in improving product quality and services to meet customer needs. This study aims to identify and analyze the needs of customers of Fruit Salad SMEs in Batam City and formulate quality improvement strategies using the House of Quality (HoQ) tool. Data were obtained through surveys and analyzed using Pearson correlation to ensure validity and reliability. The results show that all items have a significant correlation with the total score, with correlation values ranging from 0.697 to 0.860 and p-values < 0.05, indicating strong data validity and reliability. Specifically, the item